2016
DOI: 10.1093/arclin/acw073
|View full text |Cite
|
Sign up to set email alerts
|

Slow and Steady Does Not Always Win the Race: Investigating the Effect of Processing Speed across Five Naming Tests

Abstract: Confrontation naming test performance is related to cognitive processing speed, although the magnitude of this effect varies by the demands of each naming test (i.e., largest for RPN; smallest for VNT). Thus, results argue that processing speed is important to consider for accurate clinical interpretation of naming tests, especially in the context of cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Similarly, Rogalski, Peelle, and Reilly (2011) tested a sample of young adults ( N = 20, aged 18–26 years) and a sample of older adults ( N = 23, aged 54–81 years) in a picture-naming task and two processing speed tasks (Trail Maker, TMT-A and TMT-B; Reitan & Wolfson, 1985). Consistent with the results obtained by Soble et al (2016), they found that approximately 25% of the variance in picture-naming latencies was accounted for by processing speed. Verhaegen and Poncelet (2013) reported that both general processing speed and naming speed declined with age, but did not quantify the relationship between the two skills.…”
Section: The Choice Of Linguistic and Nonlinguistic Taskssupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, Rogalski, Peelle, and Reilly (2011) tested a sample of young adults ( N = 20, aged 18–26 years) and a sample of older adults ( N = 23, aged 54–81 years) in a picture-naming task and two processing speed tasks (Trail Maker, TMT-A and TMT-B; Reitan & Wolfson, 1985). Consistent with the results obtained by Soble et al (2016), they found that approximately 25% of the variance in picture-naming latencies was accounted for by processing speed. Verhaegen and Poncelet (2013) reported that both general processing speed and naming speed declined with age, but did not quantify the relationship between the two skills.…”
Section: The Choice Of Linguistic and Nonlinguistic Taskssupporting
confidence: 83%
“…Two studies have directly assessed the relationship between general processing speed and picture-naming speed in older adults. Soble et al (2016) conducted a study with a sample ( N = 60) of healthy and neuro-cognitively impaired older participants and found that 26% of the variance in picture-naming latency was explained by processing speed (measured as PSI, the processing speed index of the Wechsler Adult Intelligence Scale, 4th edition, WAIS-IV; Wechsler, 2008). Similarly, Rogalski, Peelle, and Reilly (2011) tested a sample of young adults ( N = 20, aged 18–26 years) and a sample of older adults ( N = 23, aged 54–81 years) in a picture-naming task and two processing speed tasks (Trail Maker, TMT-A and TMT-B; Reitan & Wolfson, 1985).…”
Section: The Choice Of Linguistic and Nonlinguistic Tasksmentioning
confidence: 99%
“…Discussions of processing speed in linguistic research are found primarily in studies of aging and language, given that a slowing in processing speed is a well-established component of cognitive aging (Eckert, 2010;Rogalski et al, 2011;Salthouse, 1996;Soble et al, 2016). However, processing speed correlates with picture naming, auditory lexical decision, and idiom processing in young adults as well (Hintz et al, 2020;Tilmatine et al, 2021).…”
Section: Processing Speedmentioning
confidence: 99%
“…Performance on NAB-N and BNT-2 were both significantly related to semantic fluency. Soble et al (2016) suggest the BNT-2 may involve greater visual perceptual demands than NAB-N. The visual perceptual demands of three confrontation naming tests, including BNT-2, NAB-N, and the Visual Naming Test (Hamberger & Seidel, 2003) were examined in a clinical sample of veterans (M age = 58.6 years; n = 106).…”
mentioning
confidence: 99%
“…This converges with the findings of Yochim et al (2009), who found that the correlation between the Judgment of Line Orientation (JLO; Benton, Varney, & Hamsher, 1978) and BNT-2 (r = .49) is stronger than the correlation between JLO and NAB-N (Form 1: r = .35; Form 2: r = .20). Soble et al (2016) hypothesized this may be related to differences in test stimuli, with the BNT-2 stimuli consisting of black and white drawings and NAB-N stimuli consisting of full color photographs. Yochim, Rashid, Raymond, and Beaudreau (2013) compared the frequency with which words on BNT-2 and NAB-N are used in everyday language.…”
mentioning
confidence: 99%